The Linguistic Status of Bahasa Tansi in Sawahlunto - Hanie, Nurul; Jufrizal, Jufrizal (English Language and Literature, 2024)
The linguistic status refers to how a language is classified within the linguistic landscape, indicating whether it is considered a distinct language or a variation of another language based on its linguistic characteristics. This research aimed to analyze the linguistic status of Bahasa Tansi from a linguistic perspective using a descriptive method. The study focused on the phonetic, phonological, morphological, and syntactic features of Bahasa Tansi. The findings reveal that Bahasa Tansi is identified as Tansi Creole in West Sumatra. This determination is based on a comparative analysis of 206 words from the Swadesh list between Bahasa Tansi and standard Minangkabau, questionnaire and supported by interview responses. The Swadesh list analysis, calculated using the dialectometry formula, reveals a 21.8% lexical difference and a 71.3% difference in phonetic and phonological features between Bahasa Tansi and the Minangkabau language. Additionally, the questionnaire results highlight unique morphological features in Bahasa Tansi, specifically simpler affixes compared to Bahasa Indonesia, while its syntactic features share similarities with Bahasa Indonesia. Interview responses further corroborate the distinctiveness of Bahasa Tansi as a separate language from both Minangkabau and Bahasa Indonesia. Consequently, this study concludes that Tansi is considered as a creole in West Sumatera. Key words: Language Variations, Language Status, Bahasa Tansi, Creole.